Surgical Outcomes of Endoscopic Endonasal Surgery in 29 Patients with Craniopharyngioma - Iranmehr, Arad; Esmaeilnia, Mostafa; Afshari, Khashayar; Sadrehosseini, Seyed Mousa; Tabari, Azin; Jouibari, Morteza Faghih; Zeinalizadeh, Mehdi (Journal of Neurological Surgery Part B: Skull Base, 2020)
Background Recently the endoscopic endonasal surgery (EES) has been introduced as a modality for the treatment of patients with craniopharyngiomas. In this study, we describe our initial experience in treatment of 29 patients with craniopharyngiomas using this approach.Methods Twenty-nine consecutive patients with craniopharyngiomas who had undergone EES in a 5-year period were studied retrospectively. Patients underwent preoperative and postoperative endocrinologic and ophthalmologic evaluations. Radiologic characteristics of tumors and extent of resection were determined. The recurrence and complications were evaluated.Results Pituitary and visual dysfunction were observed preoperatively in 89.7 and 86% of patients, respectively. After EES, visual outcome either showed an improvement or else remained unchanged in 92.3% of the cases; however, pituitary function remained unchanged and even got worsened in 34.6% of the cases. Prevalence of diabetes insipidus before and after surgery was 58.6 and 69.2%. The rate of gross total resection was 62%. Moreover, 86.2% of the tumors were almost totally resected (more than 95% of the tumor size resected). After surgery, cerebrospinal fluid (CSF) leak and meningitis occurred in four (13.8%) and two (6.9%) patients, respectively. Perioperative mortality was seen in two of the cases (6.9%). The mean follow-up was 25 months and tumor recurrence was discovered in four patients (15.3%).Conclusion The EES with the goal of maximal and safe tumor resection could be used for the treatment of most craniopharyngiomas. Although the rates of visual improvement and gross tumor resection are high, CSF leak, pituitary dysfunction, and meningitis are serious concerns.
Keywords: endoscopic endonasal surgery; craniopharyngioma; outcome; complication